Indian foreign policy : theory and practice - Gupta, M. G. (Mumbai : Y. K., 1985)
Contributed articles presented at a national seminar; covering predominantly post 1984 period.
Includes bibliographical references.
Keywords: India -- Foreign relations -- 1984- -- Congresses